Technically Not Life: How De Facto Life Sentences Condemn Juveniles to Die in Prison - Laugalis, Victoria Rivera (Criminal justice review, 2025)
The U.S. Supreme Court's decision in Jones v. Mississippi reignited interest in the constitutionality of lengthy prison sentences for juveniles. A substantial proportion of juveniles convicted of homicide and nonhomicide are currently serving “virtual life” or “de facto life” sentences. De facto life sentences are lengthy sentences that may be considered the equivalent of a life sentence. This article investigates how states’ statutory schemes and appellate court decisions have allowed for the use of de facto life sentences for juveniles convicted of homicide as well as nonhomicide offenses. By employing content analytical techniques, this article identifies the variation in how de facto life sentences are defined and applied across the states. Nearly every state imposes some type of de facto life sentence on juveniles, suggesting that the time is ripe for courts to determine whether these “virtual life” terms adhere to the Court's Eighth Amendment's prohibition against cruel and unusual punishment.